A evolução do instituto jurídico da propriedade: da perspectiva do individualismo à compatibilização socioambiental - Vieira, Gabriel Antonio de Abreu (2011)
In the Western world, the legal form of ownership results from a set of ideological, cultural circumstances, economic, political and natural havidas throughout history. In this sense, the objective of this study is to investigate the evolution of the legal institution of property: from individualism to social and environmental compliance perspective focusing specifically on real estate in rural and urban areas. The methodology is based on qualitative research literature, comprising the selection process and analysis of the historical evolution, theories, laws and judicial decisions that are related to the theme, using the deductive method, inductive, dialectical and dialogical . Thus, the analysis is carried out of the property that involves the formation of its meaning in antiquity, the conceptual elaboration in the second period of the Middle Ages, the development of individualistic perspective on modernity, its enhancement in liberal ideology, the issues raised for the care of the common good, the construction of the theory of social function and its situation today when the functional dimension is expanded to consider the ecological balance, and object d incidence of public policies in order to harmonize the due performance of its functions and carry out the social and environmental compatibility. The Brazil, in line with this perspective has constitutional guidelines and legislation concerning public policy, which interpreted in a systematic and teleological way, aims to reduce social inequalities and to promote the proper use of the environment, reconciling the need for economic development with ecological balance, aimed at healthy living that benefits both the present, the future generations.